2019
DOI: 10.1186/s12938-019-0685-7
|View full text |Cite
|
Sign up to set email alerts
|

Imaging modalities to diagnose carotid artery stenosis: progress and prospect

Abstract: In the past few decades, imaging has been developed to a high level of sophistication. Improvements from one-dimension (1D) to 2D images, and from 2D images to 3D models, have revolutionized the field of imaging. This not only helps in diagnosing various critical and fatal diseases in the early stages but also contributes to making informed clinical decisions on the follow-up treatment profile. Carotid artery stenosis (CAS) may potentially cause debilitating stroke, and its accurate early detection is therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 129 publications
1
64
0
4
Order By: Relevance
“…The collected data were processed by ADW4. 6 and its stability for atherosclerosis is much higher than that of arterial lumen stenosis 14 , so we further analyze the composition of plaque. Using the improved APQ non-calcified plaque detection technique, the plaque was divided into calcified plaque, non-calcified plaque and mixed plaque.…”
Section: Image Reconstruction and Data Post-processingmentioning
confidence: 99%
“…The collected data were processed by ADW4. 6 and its stability for atherosclerosis is much higher than that of arterial lumen stenosis 14 , so we further analyze the composition of plaque. Using the improved APQ non-calcified plaque detection technique, the plaque was divided into calcified plaque, non-calcified plaque and mixed plaque.…”
Section: Image Reconstruction and Data Post-processingmentioning
confidence: 99%
“…The degree of stenosis = (1 the lumen area of the lesion site / the lumen area of the control site) x100%. It is found that the risk of plaque composition and its stability for atherosclerosis is much higher than that of arterial lumen stenosis 14 , so we further analyze the composition of plaque. Using the improved APQ non-calcified plaque detection technique, the plaque was divided into calcified plaque, non-calcified plaque and mixed plaque.…”
Section: Image Reconstruction and Data Post-processingmentioning
confidence: 99%
“…Степень стеноза ВСА, в %, как отношение величины разности истинного просвета и должного на уровне стеноза, к должному (несуженному), рассчитывалась по методике ECST [5,7,8].…”
Section: материал и методыunclassified
“…В то же время при своевременном раннем выявлении атеросклеротического стенозирования коррекция его с помощью эндоваскулярных технологий в состоянии вернуть прогноз жизни и трудоспособности как минимум на средне-популяционный уровень [3,4]. Поэтому поиск наиболее диагностически и прогностически значимых характеристик сужения гемодинамического просвета артерий головного мозга сохраняет сегодня свою не только научную, но в первую очередь социально-экономическую актуальность [3,5].…”
unclassified
See 1 more Smart Citation